Professors and Publishing in the Electronic Academy - Flora G. Shrode (Issues in Science and Technology Librarianship)
This article summarizes the Professors and Publishing in the Electronic Academy Conference, which took place September 17-19, 1996 at the University Libraries at the University of Tennessee Knoxville.